Crystal structure of atorvastatin calcium trihydrate Form I (Lipitor®), (C33H34FN2O5)2Ca(H2O)3. Issue 2 (June 2020) - Hodge, Ryan L.; Kaduk, James A.; Gindhart, Amy M.; Blanton, Thomas N.
Abstract : The crystal structure of atorvastatin calcium trihydrate (ACT) has been solved and refined using synchrotron X-ray powder diffraction data and optimized using density functional theory techniques. ACT crystallizes in space group P 1 (#1) with a = 5.44731(4), b = 9.88858(16), c = 29.5925(10) Å, α = 95.859(3), β = 94.211(1), γ = 105.2790(1)°, V = 1521.277(10) Å 3, and Z = 1. The most prominent feature of the crystal structure is a hydrophilic layer parallel to the ab -plane. The atorvastatin anions bond to each side of the hydrophilic layer, forming a triple layer. The calcium coordination is distorted octahedral, with the CaO6 coordination sphere being comprised of four carboxylate oxygens, one coordinated water molecule, and a hydroxyl group from one but not the second atorvastatin anion. Several O–H⋯O hydrogen bonds form a two-dimensional network parallel to the ab -plane. The powder pattern has been submitted to ICDD ® for inclusion in the Powder Diffraction File™.